Targeting executioner procaspase-3 with the procaspase activating compound B-PAC-1 induces apoptosis in multiple myeloma cells - Zaman, Shadia (Exp Hematol, 2015)
Multiple myeloma (MM) is a plasma cell neoplasm that has a low apoptotic index. We investigated a new class of small molecules that target the terminal apoptosis pathway, called procaspase activating compounds (PACs), in myeloma cells. PAC agents (PAC-1 and B-PAC-1) convert executioner procaspases (procaspase-3, -6 and -7) to active caspase-3, -6, and -7, which cleave target substrates to induce cellular apoptosis cascade. We hypothesized that targeting this terminal step will overcome survival and drug-resistance signals in myeloma cells and induce programmed cell death. Myeloma cells expressed executioner caspases. In concert, our studies demonstrated that B-PAC-1 is cytotoxic to chemotherapy resistant or sensitive myeloma cell lines (n=7) and primary patient cells (n=11). Exogenous zinc abrogated B-PAC-1-induced cell demise. B-PAC-1-treatment-induced apoptosis was similar in the presence or absence of growth-promoting cytokines such as interleukin-6 and hepatocyte growth factor. Presence or absence of anti-apoptotic proteins such as BCL-2, BCL-X(L), or MCL-1 did not impact B-PAC-1-mediated programmed cell death. Collectively, our data demonstrate the proapoptotic effect of B-PAC-1 in MM and suggests that activating terminal executioner procaspase-3, -6 and -7 bypasses survival and drug-resistance signals in myeloma cells. This novel strategy has the potential to be an effective anti-myeloma therapy.